Cover Picture: Electrooxidation of Ethylene Glycol and Glycerol on Pd‐(Ni‐Zn)/C Anodes in Direct Alcohol Fuel Cells (ChemSusChem 3/2013). Issue 3 (4th March 2013) - Marchionni, Andrea; Bevilacqua, Manuela; Bianchini, Claudio; Chen, Yan‐Xin; Filippi, Jonathan; Fornasiero, Paolo; Lavacchi, Alessandro; Miller, Hamish; Wang, Lianqin; Vizza, Francesco
<x xml:space="preserve">Abstract</x> The cover image highlights the research carried out by the group of Francesco Vizza at ICCOM‐CNR in Florence, which is reported on page 518. It shows a direct alcohol fuel cell (DAFC) that converts alcohols into various oxygenate products, providing at the same time excellent power densities, thus exploiting the ability of the anode electrocatalyst to bring about the partial oxidation of either ethylene glycol (EG) or glycerol (G) with high selectivity and fast kinetics. The power densities obtained in the temperature range from 20 to 80 °C, with palladium loadings at the anode as low as 1 mg cm−2, show that Pd‐(Ni‐Zn)/C can be classified as the best performing palladium‐based electrocatalyst ever reported for EG and G electro‐oxidation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>